HIV–HPV Co-Infection and Identification of Novel High-Risk HPV Among Women at Two Hospital Centers in Cotonou, Republic of Benin - Clémence D. Gouton; Ifeoluwa O. Bejide; Oludayo O. Ope-ewe; Marius Adjagba; Simon Azonbakin; Gaonyadiwe Muzanywa; Florence T. Akinyi; Arnaud Agbanlinsou; Yanique Goussanou; Onikepe Folarin; Anatole Laleye; Christian T. Happi; et al. (Viruses)
Persistent high-risk human papillomaviruses (HR-HPVs) infection is the leading cause of cervical cancer. With over 200 circulating genotypes, HPV detection, management, and prevention remain challenging. In Benin, HPV prevalence and genotype distribution are largely unknown, and no national HPV vaccination program exists. This study investigates the prevalence, genotypic diversity, and risk factors of HIV–HPV co-infection among women in Cotonou, Benin. Cervical swabs were collected from 100 women living with HIV (WLWHIV) and 51 women without HIV (WWHIV) at two hospitals. DNA extraction and nested polymerase chain reaction (PCR) were used to detect HPV, followed by Sanger sequencing for genotyping. Chi-squared analysis was used to assess risk factors. HPV was detected in 85% (85/100) of WLWHIV and 60.8% (31/51) of WWHIV (p = 0.002), confirming HIV as an independent risk factor. Fifteen HR-HPV genotypes were identified, with HPV 45 most prevalent in WLWHIV and HPV 16 in WWHIV. Notably, HR-HPV 67, 70, and 82 were detected for the first time in Benin. Unmarried status and detectable HIV load were significant risk factors for co-infection. The high HPV prevalence, particularly among WLWHIV, underscores the urgent need for HPV surveillance and vaccination in Benin. Identifying novel HR-HPV genotypes highlights the necessity for ongoing monitoring and targeted prevention strategies.